Zone I of Tear Microdesiccates Is a Lipid-Containing Structure. Issue 2 (February 2017) - Traipe, Felipe; Traipe, Leonidas; Salinas-Toro, Daniela; López, Daniela; Valenzuela, Felipe; Pérez, Claudio; Cartes, Cristian; Zuazo, Francisca; Varela, Patricia; Toledo-Araya, Héctor; López-Solís, Remigio
Abstract : Purpose: Morphological features of tear microdesiccates on glass surfaces have been associated with tear fluid status. Tear-film lipids play a critical role in the pathophysiology of some ocular surface disorders. Tear microdesiccates display 4 distinctive morphological domains (zones I, II, III, and transition band). In this study, we investigated the lipid location in tear microdesiccates. Methods: Tear from individual healthy eyes (assessed by symptoms, signs, and slit-lamp examination) was collected using absorbing minisponges. One-µL aliquots were allowed to dry under ambient conditions on microscope slides. Tear microdesiccates were examined by various transmitted light microscopy methods. Tear lipids were located both by partition experiments using 2 lipophilic dyes (Oil red O and Nile blue A) mixed with tear fluid under conditions preserving morphological features of microdesiccates and by assessing the effect of 2 solvents markedly differing in polarity (water and ethanol) on the morphology of particular domains of preformed microdesiccates. Results: During desiccation, both Nile blue A and Oil red O became preferentially located in the outermost domain of tear microdesiccates (zone I) without affecting the formation of major fern-like crystalloids (zones II and III). Low volumes of water drastically affected fern-like crystalloids, whereas the gross morphology of zone I was maintained. Contrarily, ethanol, a less polar solvent, was a fixative for fern-like crystalloids, although it markedly affected the bulk of zone I by extracting liquid droplets out of microdesiccates and visibilizing some filamentous subcomponents. Conclusions: Zone I is a hydrophobic domain, whereas zones II and III are highly hydrophilic domains of tear microdesiccates. Zone I represents a lipid-rich structure.